2019
DOI: 10.25047/jtit.v4i2.68
|View full text |Cite
|
Sign up to set email alerts
|

Prototype Smart Instrument Untuk Klasifikasi Penyakit Hipertensi Berdasarkan JNC-7

Abstract: High blood disease or famous to known as hypertension almost 95% the cause is very difficult  to know. One way to know the condition of our health is by checking routine to the nearest clinic or hospital. Hypertension is one of the risk factors for dangerous diseases, such as stroke, heart attack, and kidney failure. Hypertension can cause high morbidity (pain) and mortality (death), hypertension is often called silent killer disease. People with Hypertension rarely show early symptoms, and their recognition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Primary HT is an HT condition with an unknown cause and tends to occur at 25-55 years old. At the same time, secondary HT can be controlled with medication or surgery because the aetiology and pathophysiology can be found, for example, renovascular, renal parkin, endocrine, and Cushing's syndrome (Irawan et al, 2019).…”
Section: Hypertension Conceptmentioning
confidence: 99%
“…Primary HT is an HT condition with an unknown cause and tends to occur at 25-55 years old. At the same time, secondary HT can be controlled with medication or surgery because the aetiology and pathophysiology can be found, for example, renovascular, renal parkin, endocrine, and Cushing's syndrome (Irawan et al, 2019).…”
Section: Hypertension Conceptmentioning
confidence: 99%
“…Based on diagnostic data in the Basic Health Research [3] conducted by doctors, it was found that the prevalence of hypertension in Indonesia in adolescents aged 18 years was 34.1%, while in the 31-44 year age group, it was 31.6 %, in the age group 45-54 years 45.3 %, and 55-64 years 55.2 %. In addition, there are other tools used for measuring blood pressure, namely the sphygmomanometer, but in its use, it A d v n c e d o n l i n e a r t i c l e requires supporting tests [4]. Hypertension can be detected through biomarkers (biological markers) in the human body.…”
Section: Introductionmentioning
confidence: 99%